Contrast-agent free evaluation of cardiomyopathies with T1 mapping and the new fast strain-encoded (fSENC) magnetic resonance imaging. (25th November 2020) - Hirschberg, K; Paul, O; Salatzki, J; Andre, F; Riffel, J; Ochs, M; Vago, H; Merkely, B; Katus, H.A; Friedrich, M
Abstract: Background: Cardiomyopathies (CMP) may cause impairment of cardiac function and structure. Cardiac Magnetic Resonance Imaging (CMR) is used for analysis and risk stratification of CMP by Late Gadolinium Enhancement (LGE). However, T1 mapping (T1) and fast strain encoded (f-SENC) sequences allow contrast-free and faster exams. The aim of this study was to characterize CMP by T1 and f-SENC to develop a faster and safer CMR protocol (fast-CMR). Methods: CMP scans from our CMR database were retrospectively analyzed. All patients were scanned at 1.5T/3T scanner. Study groups were divided as follows: Patients with normal findings, dilated cardiomyopathy (DCM), hypertrophic cardiomyopathy (HCM), hypertensive heart disease (HHD) and cardiac amyloidosis. Global T1 times, longitudinal (GLS) and circumferential (GCS) strain using f-SENC of study groups were compared to healthy individuals (controls). Scan time and amount of gadolinium-based contrast agent (CA) in CMR-protocol with LGE were compared to fast-CMR. Results: 174 patients and 31 controls were recruited. T1 times, GLS and GCS were similar between controls and normal individuals. T1 times were significantly increased (p<0.05), while GLS and GCS were significantly reduced (p<0.05) in all CMR study groups compared to controls (Table 1). Using fast-CMR 21 (±6) min of scan time were saved, about 47%, and 9 (±2) ml of CA were saved per patient. Conclusion: Normal findings could be identified by fast-CMR without contrast agent. Fast CMR might also be a useful tool to identify different forms of CMP. Funding Acknowledgement: Type of funding source: None